Notes to Philosophy 167: Class 4 -- Kepler's Planetary System and the Rudolphine Tables -- Complete. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Kepler's Astronomical Work Following Astronomia Nova -- Some Philosophic Issues Concerning Kepler's "Laws" -- An Examination of the Evidence for Kepler's "Laws" -- Kepler's Methodological Legacy: Some Final Remarks -- Select Sources.; Section: Class 4, Complete.